Conservation and restoration of two wall painting fragments by Bernardino Luini - Giulia Gregori (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The study focuses on the analysis of the technique of execution and phenomena of degradation, aimed at the resolution of the serious conservation problems induced by wooden boards. Thanks to technical analysis and a targeted multispectral diagnostic and scientific campaign performed on two detached fragments of the wall paintings, new containment structure systems were studied, which could also be useful for the restoration of the extant fragments of the fresco cycle in Milan.